Metode Kualitatif dan Kuantitatif dalam Penelitian Pendidikan - Hisaanah, Khauranina; Hayadi, B. Herawan; Nurlena, Elin; Zikriyanto, Wahyu; Oktalia, Huda; Suryo P, M. Wachid (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Educational research can be conducted using quantitative and qualitative approaches. This study aims to explain the characteristics and differences between quantitative and qualitative methods in educational research. The method used in this study is a literature review by examining various relevant scientific sources. The results show that quantitative methods use numerical data and statistical analysis to examine relationships between variables, while qualitative methods use descriptive data to understand educational phenomena in depth. These two approaches differ in terms of data types, data collection techniques, and analysis methods; however, both can complement each other in educational research.